PREVALENCE OF HYPOCALCEMIA IN INFANT OF DIABETIC MOTHER - ALI , A; QURATULAIN, S; FAROOQ, MU; LIAQAT, A (Biological and Clinical Sciences Research Journal, 2024)
Calcium plays an important role in the body, such as in the contraction of muscles, the transmission of nerve impulses and the calcification of bones, blood clotting, blood vessel constriction, cell division, cell membrane stability, lipid metabolism, and other essential metabolic processes. Objective: The main objective of the study is to find the prevalence of hypocalcemia in infants of diabetic mothers. Methods: This prospective observational study was conducted at National Institute of Child and Health Karachi during January 2024 to June 2024.Data were collected from 255 infants whose mothers were suffering from DM.Data were collected through a designed questionnaire which include all information related to demographics, age, history of DM and other comorbidities. Maternal data included the type of diabetes (gestational or pregestational), maternal glycemic control measured by HbA1c levels, maternal vitamin D status, and the presence of any other comorbidities, such as hypertension or obesity. Results: Data were collected from 255 infants with 31.4% born preterm and 68.6% born full-term. The majority of the infants (76.5%) had a normal birth weight (≥ 2.5 kg), while 23.5% had a low birth weight (< 2.5 kg). In terms of gender distribution, the cohort was nearly balanced, with 51.0% male and 49.0% female infants. Regarding the mode of delivery, 54.9% were delivered via cesarean section, and 45.1% were born through vaginal delivery. Infants born to mothers with poor glycemic control (HbA1c > 7%) had a higher prevalence of hypocalcemia (38.3%) compared to those with better control (19.3%). Maternal vitamin D deficiency also contributed to the risk, with 42.4% of infants affected. Neonatal hypoglycemia was strongly associated with hypocalcemia, with a prevalence of 40.0% in hypoglycemic infants. Conclusion: This study concludes that hypocalcemia is prevalent among infants of diabetic mothers (IDMs), with poor maternal glycemic control and vitamin D deficiency being significant risk factors. Early detection through routine screening, particularly in those with neonatal hypoglycemia, is essential as many cases are asymptomatic. Timely calcium supplementation effectively resolves the condition, emphasizing the importance of optimizing maternal care and standardized neonatal monitoring to improve outcomes in this high-risk population.